1956
DOI: 10.1104/pp.31.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Phosphorus Nutrition to the Translocation of 2,4-Dichlorophenoxyacetic Acid in Tomato Plants

Abstract: It has frequently been observed that the effectiveness of such herbicides as 2,4-dichlorophenoxyacetic aeid (2,4-D) Immediately after measuring the curvatures, the 10 plants in each series which had received the C14-labeled 2,4-D were harvested. The roots of these plants were washed free from the sand in which they were growing and any unabsorbed 2,4-D was washed off the treated leaves with a small stream of 70 % ethanol followed by distilled water. The treated leaf was then severed from the rest of the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1957
1957
1985
1985

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…A number of papers take up this subject. It has been shown for potassium and phosphorus that a nutritional deficiency may be a limiting factor (97,99). Temperature, formulation, the use of surfactants, place of application, etc., are other im portant factors (2,20,52,70,127).…”
Section: Movement Of Applied Substancesmentioning
confidence: 99%
“…A number of papers take up this subject. It has been shown for potassium and phosphorus that a nutritional deficiency may be a limiting factor (97,99). Temperature, formulation, the use of surfactants, place of application, etc., are other im portant factors (2,20,52,70,127).…”
Section: Movement Of Applied Substancesmentioning
confidence: 99%
“…Scott (9) found that application of potassium to potassium-deficient morning glory and zinnia plants three days before treatment with 2,4-D resulted in a significant decrease in elongation of the main axis as compared with similarly treated plants given potassium at the time of application of 2,4-D. More The radioautograms (fig 1) indicated that a considerable amount of radioactive material moved through the stems, hypocotyls, and even into the roots of most of the plants which were given potassium three days before the labeled 2,4-D was applied to them. The movement of radioactive material was considerably greater in those plants which received potassium 8 hours before application of the 2,4-D-1-C14 than in those which received the potassium later but was less than in those plants which received the potassium three days before. Six of the plants which received potassium 8 hours before application of the 2,4-D had radioactive material in the roots, whereas no plants which received potassium later exhibited this condition.…”
mentioning
confidence: 88%
“…has been shown to have a marked effect on the translocation of this plant growth regulator (8). Scott (9) found that application of potassium to potassium-deficient morning glory and zinnia plants three days before treatment with 2,4-D resulted in a significant decrease in elongation of the main axis as compared with similarly treated plants given potassium at the time of application of 2,4-D. More The radioautograms (fig 1) indicated that a considerable amount of radioactive material moved through the stems, hypocotyls, and even into the roots of most of the plants which were given potassium three days before the labeled 2,4-D was applied to them.…”
mentioning
confidence: 99%
“…Rohrbaugh and Rice [23] found less stem curvature and accumulation of ~4C-2,4-D in roots of tomato (Lycopersicon esculentum Mill.) plants deficient in P than in plants grown with adequate P. Baird et al [1] reported that application of N to quackgrass (Agropyron repens L.) 30 days prior to treatment with glyphosate significantly improved control, which was attributed to greater herbicide translocation resulting from increased vegetative growth.…”
Section: Introductionmentioning
confidence: 99%